Hyperimmunoglobulin E syndrome presenting as osteogenesis imperfecta in a 3 year old child - Stephen Gorgas; Walid Abuhammour; R. Alexander Blackwood (MDPI AG, 2013)
We present a case of hyperimmunoglobulin E (hyper-IgE) syndrome in a three year old boy. There are many pitfalls in diagnosing this disease in the very young population, mainly due to the ambiguity of some diagnostic criteria in this population. Recognizing this syndrome early in life can potentially be very beneficial to the patients involved and the medical system as a whole. Early diagnosis can lead to fewer diagnostic tests, fewer referrals, and more focused exams, thus potentially reducing medical cost while also reducing the number of serious infections later in life, including those which are potentially fatal. Additionally, a well-known association between lymphoma and hyper-IgE syndrome has been established; while no recommendations are currently in place for screening, early diagnosis could help medical providers have a higher threshold for diagnosis of this disease.